2017
DOI: 10.3389/fpsyg.2017.01620
|View full text |Cite
|
Sign up to set email alerts
|

The Holistic Processing Account of Visual Expertise in Medical Image Perception: A Review

Abstract: In the field of medical image perception, the holistic processing perspective contends that experts can rapidly extract global information about the image, which can be used to guide their subsequent search of the image (Swensson, 1980; Nodine and Kundel, 1987; Kundel et al., 2007). In this review, we discuss the empirical evidence supporting three different predictions that can be derived from the holistic processing perspective: Expertise in medical image perception is domain-specific, experts use parafoveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 122 publications
(220 reference statements)
2
78
0
2
Order By: Relevance
“…Namely, in more than half of trials, radiologists did not change the location of slices on the display and inspected the entire three-dimensional image. This approach might be consistent with the global processing of visual information, which is a characteristic feature of radiologists' perception, previously reported for medical image reading [41]. According to this approach, experienced radiologists effectively use their parafoveal and peripheral vision to obtain a global impression of the image in contrast to novices who mostly focus on details and rely more on foveal vision.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Namely, in more than half of trials, radiologists did not change the location of slices on the display and inspected the entire three-dimensional image. This approach might be consistent with the global processing of visual information, which is a characteristic feature of radiologists' perception, previously reported for medical image reading [41]. According to this approach, experienced radiologists effectively use their parafoveal and peripheral vision to obtain a global impression of the image in contrast to novices who mostly focus on details and rely more on foveal vision.…”
Section: Discussionsupporting
confidence: 86%
“…The ability of experienced radiologists to engage in the global processing of the entire image is another piece of evidence for their tuned visual perception. Namely, experts can process large regions of the image in parallel using their parafoveal and/or peripheral vision [41]. The psychophysical assessment of perceptual expertise has revealed that experienced radiologists can quickly extract the relevant information from the complete visual scene, guiding their selective visual attention efficiently, and further conducting a more organized visual search when compared to their less-experienced colleagues.…”
Section: Ergonomic Evaluation Of Visualization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One demonstration of holistic processing involves focusing on the overall stimulus and then very quickly honing in on only the most relevant details for making an informed decision. Holistic processing is exemplified by radiologists looking first at an entire CT image before narrowing in quickly on the parts of the image that are consistent with lesions (Wood, 1999;Sheridan and Reingold, 2017), or car experts first looking at the car as a whole before zeroing in on the aspects that identify the unique make and model of the vehicle (Gauthier et al, 2000;Sunday et al, 2018b). Further, these visual ability metrics and fluid intelligence are both associated with successful performance on a visual detection task in radiological images (Sunday et al, 2018a) and performance on these tasks has been linked with specific activation in the fusiform face area, an area associated with expertise (Gauthier et al, 1999;Tarr and Gauthier, 2000;Gauthier and Nelson, 2001;Sunday et al, 2018b).…”
Section: Holistic Processing In Social Interactionsmentioning
confidence: 99%